2009
DOI: 10.1007/s11032-009-9272-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of SNP markers and haplotype analysis of the candidate gene for rhg1, which confers resistance to soybean cyst nematode in soybean

Abstract: Soybean cyst nematode (SCN; Heterodera glycines Ichinohe) is one of the most destructive pests in the cultivation of soybean (Glycine max (L.) Merr.) worldwide. Markers based on the SCN resistance gene will enable efficient marker-assisted selection (MAS). We sequenced the candidate gene rhg1 in six resistant and two susceptible soybean genotypes and identified 37 SNPs (single nucleotide polymorphisms) among the sequences, of which 11 were in the coding region. Seven of these 11 SNPs led to changes in the amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 40 publications
0
21
1
Order By: Relevance
“…Compared to the findings in rhg1 reported by Li et al (2009), who identified 37 SNPs and 5 InDels among 8 resistant G. max genotypes, we identified 70 SNPs and 8 InDels, among which 32 SNP loci were shared. For Rhg4, however, we only identified 9 SNPs, which was less than the 31 SNPs among 76 G. max genotypes found in the same sequence region by Yuan et al (2012).…”
Section: Dna Polymorphism Among 23 G Soja Resistant Accessionscontrasting
confidence: 53%
See 2 more Smart Citations
“…Compared to the findings in rhg1 reported by Li et al (2009), who identified 37 SNPs and 5 InDels among 8 resistant G. max genotypes, we identified 70 SNPs and 8 InDels, among which 32 SNP loci were shared. For Rhg4, however, we only identified 9 SNPs, which was less than the 31 SNPs among 76 G. max genotypes found in the same sequence region by Yuan et al (2012).…”
Section: Dna Polymorphism Among 23 G Soja Resistant Accessionscontrasting
confidence: 53%
“…a Glycine max resistant cultivar is underlined. Among domesticated soybean collections, the haplotypes 689 C-757 C in rhg1 and 1724 C-1760 C-2120 T-2387 G in Rhg4 were found to be predominant, and were considered to be SCN resistance-associated haplotypes (Yuan 2007;Li et al 2009). For wild soybeans, we found that, except for ZYD01185, 22 accessions possessed either one of the resistanceassociated haplotypes or both.…”
Section: Haplotypes Of G Soja Accessions and G Max Resistant Accessmentioning
confidence: 76%
See 1 more Smart Citation
“…Possible roles include contributions to additive resistance; contributions to resistance in other resistance types (e.g PI88788 and Toyohazu; R types 2 and 3) or contributions to the resistance to other Hg types (Nelsen et al 2003;Li et al 2009). Unlikely, in view of the susceptibility of segregation events within the interval from the RLK to Satt309 in both PI evolution and NIL segregation, is the hypothesis that the linked genes are factors necessary in susceptible genotypes for SCN parasitism.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the robust marker-phenotype associations are required for successful MAS. Soybean SNP and SRR markers are often more robust and with higher resolution to detect a specific allele in the population (Coryell et al, 1999;Zhu et al, 2003;Hyten et al, 2008;Li et al, 2009;Hyten et al, 2010). Even one marker alone can be extremely effective in screening breeding populations.…”
Section: Mas and Qtl Cloningmentioning
confidence: 99%